Analisis Pengaruh Pembinaan Dan Keteladanan Guru Sekolah Minggu Berdasarkan Yakobus 3:1-12 Terhadap Pertumbuhan Rohani Anak-Anak Di Gereja-Gereja Bandar Lampung - Stella mulalinda (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2024)
This research is motivated by various factors that have been limited within the boundaries of the problem, namely it was found that not all Sunday School Teachers carry out good training practices, it was observed that not all Sunday School Teachers were role models and it was found that not all Sunday School Children experienced optimal spiritual growth. The purpose of this research is to examine the influence of Sunday School teachers' guidance and exemplary behavior based on James 3:1-12 on the spiritual growth of Sunday School children in churches in the Bandar Lampung area. The method used by the researcher in data collection efforts is quantitative, where questionnaires are the primary method, supported by literature review and observation methods. The population in this study consists of 80 Sunday School teachers in churches in the Bandar Lampung area. Based on the results of the multiple regression test between the three variables, it is known that there is an influence of Sunday School teachers' guidance and exemplary behavior based on James 3:1-12 (X1, X2) on the spiritual growth of Sunday School children in churches in the Bandar Lampung area (Y) with an R Square of 0.789 or 78.9%, which falls into the high category. If the influence of variable X on Y with an R Square of 78.9%, then there are still 21.1% other influencing factors. Thus, the results of the hypothesis proposed by the researcher, "it is suspected that there is an influence of Sunday School teachers' guidance and exemplary behavior based on James 3:1-12 collectively on the spiritual growth of Sunday School children in churches in the Bandar Lampung area," have been proven and accepted.